Live birth rate following oral antibiotic treatment for chronic endometritis in infertile women with repeated implantation failure. (13th June 2017) - Kitaya, Kotaro; Matsubayashi, Hidehiko; Takaya, Yukiko; Nishiyama, Rie; Yamaguchi, Kohei; Takeuchi, Takumi; Ishikawa, Tomomoto
Abstract : Problem: The aim of this prospective study was to investigate the prevalence of chronic endometritis (CE) in infertile women with a history of repeated implantation failure (RIF) and to determine whether oral antibiotic treatment improves their live birth rate in the following embryo transfer (ET) cycles. Method of study: Endometrial biopsy samples obtained from infertile women with RIF were subjected to immunohistochemistrical/histopathologic diagnosis of CE. Following antibiotic administration to the RIF/CE group, their histopathologic cure rate, microbial detection rate, and reproductive outcome in the subsequent ET cycles were prospectively studied. Results: 33.7% of infertile women with RIF were diagnosed with CE. Following the first‐line doxycycline treatment, the histopathologic cure rate in the subsequent endometrial biopsy was 92.3%. Following the second‐line metronidazole/ciprofloxacin treatment, the overall cure rate was 99.1%. The live birth rate in the first ET cycle ( P =.031, RR 1.48, 95% CI 1.03‐2.12) and cumulative three ET cycles ( P =.037, RR 1.39, 95% CI 1.02‐1.90) following antibiotic treatment in the cured RIF/CE group (32.8% and 38.8%, respectively) was significantly higher than in the RIF/non‐CE group (22.1% and 27.9%, respectively). Conclusion: Chronic endometritis was found in one‐third of infertile women with RIF. The oral antibiotic treatment against CE might be a promising therapeutic option for infertile women with RIF.